Advancing Immunization in Africa: Overcoming Challenges to Achieve the 2030 Global Immunization Targets - Okesanya OJ; Olatunji G; Olaleke NO; Mercy MO; Ilesanmi AO; Kayode HH; Manirambona E; Ahmed MM; Ukoaka BM; Lucero-Prisno III DE (Dove Medical Press, 2024)
Olalekan John Okesanya,1 Gbolahan Olatunji,2 Noah Olabode Olaleke,3 Mba Oluebube Mercy,4 Ayodele O Ilesanmi,5 Hassan Hakeem Kayode,6 Emery Manirambona,7 Mohamed Mustaf Ahmed,8 Bonaventure Michael Ukoaka,9 Don Eliseo Lucero-Prisno III10- 12 1Department of Public Health and Maritime Transport, University of Thessaly, Volos, Greece; 2Department of Medicine and Surgery, University of Ilorin, Kwara, Nigeria; 3Obafemi Awolowo University Teaching Hospital Complex, Ile-Ife, Nigeria; 4Department of Physiotherapy, David Umahi Federal University Teaching Hospital, Uburu, Nigeria; 5Department of Medical Laboratory Science, Oyo State Hospital Management Board, Oyo, Nigeria; 6Department of Medical Laboratory Science, Chrisland University, Abeokuta, Nigeria; 7College of Medicine and Health Sciences, University of Rwanda, Kigali, Rwanda; 8Faculty of Medicine and Health Sciences, SIMAD University, Mogadishu, Somalia; 9Department of Internal Medicine, Asokoro District Hospital, Abuja, Nigeria; 10Department of Global Health and Development, London School of Hygiene and Tropical Medicine, London, UK; 11Research and Development Office, Biliran Province State University, Naval, Philippines; 12Research and Innovation Office, Southern Leyte State University, Sogod, PhilippinesCorrespondence: Mohamed Mustaf Ahmed, Email momustafahmed@simad.edu.soAbstract: African immunization programs are crucial in reducing the prevalence of infectious diseases and improving public health outcomes. This review provides an overview of the current status of immunization efforts in Africa, highlights key challenges, and offers recommendations to help the continent achieve the 2030 Global Immunization Goals. While progress has been made, significant challenges remain. For instance, the WHO African Region reports full immunization coverage at 56.5%, partial coverage at 35.1%, and zero immunization coverage at 8.4%. Between 2019 and 2021, approximately 67 million children in Africa did not receive routine vaccinations, with West and Central Africa particularly affected. DTP1 coverage remained stable at 80%, but DTP3 coverage saw a slight drop to 72% between 2021 and 2022. As of 2022, MCV1 coverage reached 69%, reflecting ongoing efforts against measles. Key barriers to vaccination include limited parental education, religious beliefs, inadequate healthcare systems, and vaccine hesitancy. Addressing these barriers requires community-driven approaches like door-to-door campaigns and mobile clinics. To reach the 2030 immunization targets, health systems must be strengthened, vaccine supply chains optimized, and financial resources-both domestic and international-expanded. The Immunization Agenda 2030 (IA2030) emphasizes data-driven decision-making, nation-ownership, and tailored strategies to overcome obstacles and raise immunization coverage among several demographic groups. Achieving these 2030 goals in Africa requires collaborative efforts to ensure equitable access to vaccines, address sociocultural challenges, and strengthen health system infrastructure.Keywords: immunization, vaccination, immunity, vaccine, Africa